Analisis Bagan Aktansial Cerita Anak Jepang Urashima Taro - Susanti, Rita (Lingua Cultura, 2011)
Thisi research is a kind of a research focusing on linguistic which uses semiotic in order toÂ find out what lies behind the content of a childrenâ€™s story. The subject of this research is an ancientÂ story of a Japanese children called mukashi banashi. It comes with the title of Urashima Taro whichÂ has been translated into Indonesia Language. Through semiotic analysis, the story may be conductedÂ in a syntaxical and semantical way. According to syntax analysis, there are two episodes in the story.Â In this first episode Urashima Taro becomes the subject of the research while in the latte, the turtle isÂ the subject. We may learn that the story plott and the flow of the story have gone through a flashback process. In the structure or â€œbatihâ€, it is known that the story has a complex relationship due to itsÂ expansion plot. Based on the semantic analysis, it is also know that the main/lead character of theÂ story is Urashima Taro and the other characters are Urashima Taroâ€™s mother and the queen. TheÂ morale message of the whole story is dedicated to all children reading it.